Determinants Of Exclusive Breastfeeding In Jambi City - Kartini Apriandini; Asparian, Asparian; M.Ridwan (Sean Institute, 2024)
Exclusive breast milk (ASI) means that babies are only given breast milk for 6 months without additional liquid food such as formula milk, oranges, honey, tea and water. Coverage of exclusive breastfeeding is still low in Indonesia, namely (68%) and in Aurduri Health Center in Jambi City (39%), while the target achievement was 80%. The aim of this research is to determine the determinants of exclusive breastfeeding in the Aurduri Community Health Center Work Area in Jambi City. This research method is case control. The population in this study was 101 mothers who had babies aged 7-24 months in the Aurduri Health Center Working Area in Jamb City. The sampling technique used is accidental sampling. The number of samples was 54 people. Data analysis was carried out univariate and bivariate using the Chi-square test. The research results found that 50% of mothers gave exclusive breast milk and 50% of mothers who did not give exclusive breast milk. There is a relationship between IMD (p=0.002), health worker support (p=0.003), family support (p=0.014), and mother's employment (p=0.049) with exclusive breastfeeding. Conclusion: Exclusive breastfeeding is influenced by IMD, support from health workers, family support and mother's work